The development of the theory and practice of project management: the role of the scientific school of the State University of Management - G. Ya. Soroko; I. Z. Kogotkova (Вестник университета)
The purpose of this study is to fill the lack of coverage in the scientific literature of the processes offormation and development of domestic experience ofproject management. The results of the study of the Genesis and evolution ofproject management as a special type of management activity have been presented, the main events in the history of the formation and development of the theory and practice ofproject management as a result of scientific research of scientists of the State University of management have been highlighted.The first part of the article covers the period until the mid-70s of the last century.